New perspectives on sport and 'deviance' : consumption, performativity, and social control - Blackshaw, Tony, 1960- (Routledge, 2004)
This book awakens the sociology of sport to the possibilities of re-imagining 'deviance' and offers an evocative approach which will appeal both to academics and students alike.